Faktor-Faktor yang Mempengaruhi Persepsi Perawat tentang Kolaborasi Interprofesional di Rumah Sakit Daerah - Suharjo; Harif Fadhillah; Eni Widiastuti (Faletehan Health Journal, 2026)
Interprofessional collaboration among nurses is vital for effective healthcare, yet its influencing factors in regional hospitals remain underexplored. This study aimed to examine the effects of demographic characteristics, work experience, and workplace culture on interprofessional collaboration. A cross-sectional study was conducted in a public hospital in Banten Province, Indonesia and involved 230 registered nurses selected through purposive sampling. Data collected via structured questionnaires were analyzed using descriptive statistics, reliability analysis, and multiple linear regression. The regression model was statistically significant (F=38.47, p<0.001), explaining 52% of the variance (R2=0.52). Workplace culture was the strongest predictor (β = 0.45, p < 0.001), followed by work experience (β = 0.28, p < 0.001). Education level (β = 0.12, p = 0.042) and work unit (β = 0.10, p = 0.046) had small but significant effects, while age and gender were not significant. The findings indicate that supportive workplace culture and professional experience are important factors associated with stronger interprofessional collaboration among nurses. Hospital management may strengthen collaborative practices through mentorship programs, continuous professional development, and organizational initiatives that promote teamwork and communication.